PoreMS: a software tool for generating silica pore models with user-defined surface functionalisation and pore dimensions. Issue 4 (4th March 2021) - Kraus, Hamzeh; Rybka, Julia; Höltzel, Alexandra; Trebel, Nicole; Tallarek, Ulrich; Hansen, Niels
ABSTRACT: Mass transport under confinement is at the heart of all processes employing functionalised mesoporous silica materials, such as liquid chromatography, heterogeneous catalysis, and gas adsorption. Molecular simulation studies of mass transport in such settings require pore models that replicate the geometry, dimensions, and chemical structure of a surface-functionalised silica mesopore. We present a software tool that facilitates rapid model building of functionalised silica pores for systematic studies of confinement effects in various applications of relevant materials. The tool allows to choose the chemical structure and density of the ligands and to control the residual hydroxylation of the silica surface. Individual ligands can be placed at a user-defined position on the surface. Moreover, the tool supports an independent functionalisation of the interior and exterior pore surface. We explain each step of the pore generation, discuss the underlying assumptions and limitations, and introduce examples of generated cylindrical pore models for chromatography and catalysis.